2017
DOI: 10.1038/s41598-017-00926-x
|View full text |Cite
|
Sign up to set email alerts
|

A universal primer-independent next-generation sequencing approach for investigations of norovirus outbreaks and novel variants

Abstract: Norovirus (NoV) is the most common cause of non-bacterial gastroenteritis and is a major agent associated with outbreaks of gastroenteritis. Conventional molecular genotyping analysis of NoV, used for the identification of transmission routes, relies on standard typing methods (STM) by Sanger-sequencing of only a limited part of the NoV genome, which could lead to wrong conclusions. Here, we combined a NoV capture method with next generation sequencing (NGS), which increased the proportion of norovirus reads b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…From a virological point of view, the analysis of a larger fragment of the RdRp gene in comparison to available studies 12,13,18,19 revealed a high genetic variability of swine NoVs in North East Italy, therefore suggesting that efforts should be made in the generation of longer RdRp swine NoV sequences which are more informative. Clearly, next generation sequencing (NGS) methods, allowing full genome or nearly full genome sequencing, represents the ideal approach, as proven for human NoVs [40][41][42] and animal NoVs 43 . Whether these methods could be applicable for swine NoV, should be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…From a virological point of view, the analysis of a larger fragment of the RdRp gene in comparison to available studies 12,13,18,19 revealed a high genetic variability of swine NoVs in North East Italy, therefore suggesting that efforts should be made in the generation of longer RdRp swine NoV sequences which are more informative. Clearly, next generation sequencing (NGS) methods, allowing full genome or nearly full genome sequencing, represents the ideal approach, as proven for human NoVs [40][41][42] and animal NoVs 43 . Whether these methods could be applicable for swine NoV, should be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Reassuringly, phylogenetic clustering of these shorter RdRp sequences was identical with segregation of P-types based on the complete RdRp sequences (~1500 nt), which were available for 85 % of the sequences used in our study. Additional complete RdRp sequences or ideally complete genome sequences for all reference strains will help to improve the robustness of the present classification system for which several protocols have been described recently [54][55][56]. databases for novel genotypes and update the reference sequences accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore larger parts or whole genome sequencing approaches might be required to differentiate between sequences originating from an outbreak and sporadic cases. Since HAdVs genome consists of dsDNA, it might also be far less variable than other (ssRNA) viruses, for instance norovirus, where molecular methods are commonly used to identify point-source outbreaks [24,25]. Systematic surveillance and reporting of HAdV infections and virus genotyping would provide critical information on HAdV types commonly in circulation and their genetic diversity and also allow for the identification of clusters of infections likely to be outbreaks.…”
Section: Discussionmentioning
confidence: 99%